2021
DOI: 10.1021/acs.jpcb.0c08255
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field-Mediated Fibronectin–Hydroxyapatite Interaction: A Molecular Insight

Abstract: In experimental research-driven biomaterials science, the influence of different material properties (elastic stiffness, surface energy, etc.) and, to a relatively lesser extent, biophysical stimulation (electric/magnetic) on cell−material interactions has been extensively investigated. Despite the central importance of protein adsorption on cell−material interactions, the quantitative analysis to probe into the role of physicochemical factors in protein adsorption remains largely unexplored in biomaterials sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…It is now well-known that not all residues of FN interact equally with HA surface. Similar to our previous study, 31 the charged residues were found to be interacting more strongly with the surface (and Fig. S5 and S6 in supporting information) and have been listed in Table 2.…”
Section: Adsorbing Residuessupporting
confidence: 84%
See 2 more Smart Citations
“…It is now well-known that not all residues of FN interact equally with HA surface. Similar to our previous study, 31 the charged residues were found to be interacting more strongly with the surface (and Fig. S5 and S6 in supporting information) and have been listed in Table 2.…”
Section: Adsorbing Residuessupporting
confidence: 84%
“…Another important aspect in the context of adsorption phenomena is the protein-surface distance as a higher protein-surface distance indicates a weakly adsorbed or desorbed state. 31 In the present study, the distance between the centre of mass (COM) of FN and surface has been computed together with the minimum distance between them (Fig 3(a)). The minimum distance is defined as the minimum of all the atomic pair distances, where one atom of the pair belongs to FN and other belongs to the surface.…”
Section: (B))mentioning
confidence: 99%
See 1 more Smart Citation
“…INTERFACE force field (IFF) was used to establish interaction between the calcium/phosphate and collagen protein in the aqueous phase. [58][59][60] The first 100 ps MD simulation was used for system heating up to 310 K in the isothermal-isobaric ensemble. The next 30 ns MD simulation was performed for the data analyses in the canonical ensemble (NVT) with the integration time step of 2 fs.…”
Section: Nucleation Molecular Dynamicsmentioning
confidence: 99%
“…With the development of modern computational technology, molecular dynamics simulation has become a powerful tool for studying the interaction between the protein and material surface at the atomistic level. 62–64 However, so far, the adsorption mechanism of acetylcholinesterase on the functionalized CNTs has not been reported. In this work, the parallel tempering Monte Carlo (PTMC) 65 and all-atom molecular dynamics (AAMD) simulations were employed to study the adsorption mechanism of acetylcholinesterase on the surfaces of NH 2 –CNT, COOH–CNT and pristine CNT.…”
Section: Introductionmentioning
confidence: 99%